Prepackaged formula low-residue diet vs. self-prepared low-residue diet before colonoscopy: A multicenter randomized controlled trial - Pan, Peng; Gu, Lun; Zhao, Shengbing; Wang, Shuling; Ma, Jiayi; Fu, Hongyu; Chen, Youxiang; He, Shuixiang; Tian, Zibin; Xu, Le; Feng, Zhijie; Li, Yanqing; et al. (Frontiers in Medicine, 2023)
Background and aims Compared with self-prepared LRD, a prepackaged low-residue diet (LRD) can improve patient compliance, but whether it can further improve the quality of bowel preparation is uncertain. The study aimed to compare the application of the prepackaged formula LRD with self-prepared LRD in bowel preparation for colonoscopy. Methods A multicenter randomized controlled trial was conducted in 15 centers. The eligible subjects were randomly assigned to one of two groups: the formula LRD group and the self-prepared LRD group. On the day before the colonoscopy, subjects in the self-prepared LRD group were instructed to consume a restricted LRD prepared by themselves, while subjects in the formula LRD group were given six bags of prepackaged formula LRD and instructed to consume them according to their individual need. The primary outcome was an adequate bowel preparation rate. Secondary outcomes mainly included Boston Bowel Preparation Scale (BBPS) scores, dietary restriction compliance rate, tolerance, satisfaction, adenoma detection rate (ADR), and adverse reactions. The trial was registered at ClinicalTrials.gov under the identifier NCT03943758. Results A total of 550 subjects were recruited. Compared with the self-prepared LRD group, the formula LRD group showed a higher adequate bowel preparation rate (94.5 vs. 80.4%; P < 0.01), BBPS scores (7.87 ± 1.13 vs. 6.75 ± 1.47; P < 0.01), dietary compliance rate (92.4 vs. 78.9%; P < 0.01), tolerance (P < 0.01 in degree of hunger, intensity of physical strength, and negative influence on daily activities), satisfaction (8.56 ± 1.61 vs. 7.20 ± 2.02; P < 0.01), and ADR (25.6 vs. 16.0%; P < 0.01). There was no significant difference in adverse reactions. Conclusion Compared with self-prepared LRD, the formula LRD showed similar safety and higher bowel preparation quality, compliance, and tolerance in bowel preparation. More formula LRDs could be designed according to different dietary habits and ethnic populations, and further researches are warranted to confirm their effect. Clinical trial registration https://register.clinicaltrials.gov, identifier: NCT03943758.